Strata Data Conference 2017 : New York, New York. (O'Reilly Media, 2017)
"The Strata Data Conference New York 2017 gathered more than 340 of the world's brightest data visionaries, practitioners, and strategists to speak about today's most effective big data technologies, techniques, and business practices. This video compilation gives you a best-in-house seat for each of the conference's 21 keynotes, 22 tutorials, and 189 individual sessions, which covered topics about AI, predictive analytics, security, cloud strategy, data engineering, Hadoop, machine learning, IoT, stream processing, visualization, and more. And, like all Strata video compilations, this one is packed with revelations about big data's emerging technologies. Get this compilation and you'll be one of the first to learn about Apache Parquet, TimescaleDB, Stanford University's Weld, Twitter Heron, relational storage, Prophet probabilistic programming, PyTextRank natural language processing, the Elastic Data Platform, and much more."--Resource description page